Genetic diversity of Euterpe edulis martius based on fruit traits (Bioscience Journal, 2020)
Juçara (Euterpe edulis Martius) is a palm species from the Atlantic Forest whose fruits are important as a source of food to several individuals from the fauna of the region. Despite its ecological importance, juçara is found in the list of endangered species, due to the fragmentation of the forests and the illegal extraction of the heart of palm. We aimed to evaluate the inter- and intra-populational genetic diversity of E. edulis based on fruit and seed traits in forest fragments of the Espírito Santo State in Brazil.  The aim was to generate information to be used in E. edulis breeding programs, or in the delineation of more efficient management and reforestation strategies. The study was carried out in 20 forest fragments and 198 fruit plants were sampled. Positive genetic association was observed between the evaluated traits, with the longitudinal diameter of the fruit (LDF) and the seed mass (SM) greatly affecting fruit mass (FM). The existence of inter- and intra-populational genetic divergence was proved. The genetic divergence found in E. edulis suggests that there is genetic material that can be explored in breeding programs and this information may also contribute to management strategies that can increase the species genetic diversity.